Hubungan Disiplin Belajar dengan Kemandirian Belajar Siswa - Putri Ramadona; Yusri Yusri (Jurnal Neo Konseling, 2019)
Independence is a directed process because the development of independence is in line with the nature of human existence, the direction of development must be in line with and based on the goals of human life. But the reality in the field there are still students who have low learning independence, there are still many students who are low in the desire to compete to advance for their own good, less able to make decisions and initiatives to overcome problems, lack self-confidence in doing their tasks, and lack responsible for what he does. Independence of learning is the ability of students to realize their desires and take initiative in determining the learning activities such as formulating learning goals, learning resources (either in the form of people or materials) to diagnose learning needs and control the learning process without the help of others and one of the factors that influence it is student learning discipline. This study aims to determine the relationship between disciplines of learning with students' learning independence in Padang 2 Public High School. This research is a descriptive correlational research with quantitative methods. The total sample of 245 students was selected using the Simple Random Sampling technique. The research instruments used were learning discipline questionnaires and student learning independence questionnaires. The results of the study revealed that (1) the discipline of learning students in SMA Negeri 2 Padang was in the good category. (2) the learning independence of students in SMA Negeri 2 Padang is in a fairly good category (3) there is a significant relationship between the discipline of learning and student learning independence in SMA Negeri 2 Padang. Based on research findings, it is recommended that school counselors / counselors be able to provide guidance and counseling services, namely information services and individual counseling services in order to help students who have problems with learning independence.